CORRELATION BETWEEN PARITY, TYPE OF CHILDBIRTH AND AGE OF MATERNITY TO GIVING EARLY BREASTFEEDING INITIATION (IMD) AT LEMAHDUHUR HEALTH CENTER IN 2022 - Titin Patimah; Nanik Yuliwati (Lembaga Pengembangan Kinerja Dosen, 2023)
Background : Early Initiation of Breastfeeding (IMD) is the process of placing a newborn on the mother's chest or stomach so that the baby can naturally find its own source of breast milk or breast milk and start breastfeeding. The baby will get immunity. IMD is beneficial for mothers because it can help speed up the postpartum recovery process Research purposes : To find out the relationship between parity, type of delivery and the age of the mother to the provision of early breastfeeding initiation (IMD) at the Lemahduhur Health Center in 2022 Research methods : The type of research used in this research is quantitative with a cross sectional research design. The population in this study is168 mothers giving birth. The sample in this study were 63 mothers giving birth using the accidental sampling technique. Bivariate analysis using the chi-square test. Research result : The distribution of the frequency of parity descriptions of mothers giving birth at the Lemahduhur Health Center in 2022 is partly 1-4 times as many as 45 people (71.4%). The distribution of the frequency of descriptions of the types of maternal deliveries at the Lemahduhur Health Center in 2022 is mostly normal, with 41 people (65.1%). The frequency distribution of the description of the age of mothers giving birth at the Lemahduhur Health Center in 2022 is mostly 20-40 years, with 36 people (57.1%). The distribution of the frequency of giving Early Breastfeeding Initiation (IMD) at the Lemahduhur Health Center in 2022 is mostly yes, as many as 42 people (66.7%). Conclusion : Can be concluded thatthere isthe relationship between parity, type of delivery and the age of the mother to the provision of early breastfeeding initiation (IMD) at the Lemahduhur Health Center in 2022.